Dinoflagellate cyst distribution in the surface sediments of the coasts of Biliran and Biliran Strait, Philippines - Noroña, James Victor Ty (2022)
The non-motile cells or cysts are stages in the life cycle of dinoflagellates that play an important role in initiating and terminating harmful algal blooms (HABs). They serve as inoculum for blooms to start and can also reduce the number of motile cells through cyst-formation. Information on the composition of dinoflagellate cysts is instrumental in designing models for the prediction, mitigation, and management of HABs. This study examined the dinocyst composition and distribution on the coasts of Biliran and Biliran Strait, Philippines, areas that experience periodic HABs as reported by BFAR. Sediment samples were collected in seven stations from March 24 to 26, 2021, and were concentrated using the sieving technique. Microscopic analysis revealed a total of eight dinocysts species belonging to three orders: Gonyaulacales, Gymnodiniales, and Peridiniales. Dinocysts were detected in all stations ranging from 10-2700 cysts g raised to negative 1 DW. Pyrodinium bahamense cyst (Polysphaeridium zoharyi) were observed in 3 sites and had relatively low densities (3-10 cyst g raised to -1 DW). Spatial distribution revealed larger concentrations of dinocysts in the inner areas of the Biliran Strait than in open embayments. Cyst abundance and distribution were mainly affected by sea surface temperature and substrate type. Mariculture activities may influence sediment grain size and nutrient levels, which can affect the microbial community composition in surface sediments. Suspected viable cysts of ichthyotoxin-producing Margalefidinium polykrikoides (syn: C. polykrikoides) were observed in high densities (> 2700 cysts g raised to -1 DW) near mariculture and residential areas, indicating potential cyst seedbeds.